THEORETICAL FOUNDATIONS AND DETECTION TECHNOLOGY OF ZONES OF ABNORMALLY HIGH PRESSURES (FOR EXAMPLE, OBJECTS OF THE AZOV KUBAN CAVITY, THE KUMO-MANYCH CAVITY AND THE JUNCTION ZONE OF THE CASPIAN CAVITY AND THE KARPINSKI RIDGE) - Konstantin Sergeevich Golovanov; Vladimir Mikhailovich Kharchenko; Tatiana Vladimirovna Voloshina; Denis Igorevich Zenin (Наука. Инновации. Технологии, 2022)
This article presents the theoretical foundations (the concept of tectonic activity and the concept of the mechanism of formation of the structures of the central type and their interpretation, with an assignment of zones of compression, stretching, geodynamic centers and nodal points). It provides the specific results of interpretation of topographic maps and satellite images with detection of structures of the central type (SCT) and lineaments, the interpretation of SCT with an assignment of possible zones of abnormal high pressures on the territory of the Krupskaya area of the Azov Kuban cavity, on the Kamyshovoe and the Ravninnoe fields in the Kumo-Manych cavity, and specifically identified zones of abnormal high pressures on the Kasatkinskaya area at the junction of the Caspian cavity and the Karpinski ridge. For the first time the paper provides not only the results of decryption of aerial and satellite images and topographic maps, but also the method of their interpretation, with an assignment of regions of interference of zones of stretching, compression (prospective zones of abnormal high pressures) and nodal points or zones of subver-tical destruction, that are promising to contain oil and gas, and seismicity.